Baicalein prevents stress-induced anxiety behaviors in zebrafish model - Selvaraj, Logesh Kumar; Jeyabalan, Srikanth; Wong, Ling Shing; Sekar, Mahendran; Logeshwari, B.; Umamaheswari, S.; Premkumar, Sree; Sekar, Roshan Tej; Begum, M. Yasmin; Gan, Siew Hua; Izzati Mat Rani, Nur Najihah; Chidambaram, Kumarappan; et al. (Frontiers in Pharmacology, 2022)
Baicalein is a flavonoid mainly obtained from plants with wide range of biological activities, including neuroprotection. An acute and unexpected chronic stress (UCS) protocol has recently been adapted to zebrafish, a popular vertebrate model in brain research. The present study was aimed to evaluate baicalein's anti-anxiety potential in a zebrafish model by induction, which included neuropharmacological evaluation to determine behavioural parameters in the novel tank diving test (NTDT) and light-dark preference test (LDPT). The toxicity was also assessed using the brine shrimp lethality assay, and the 50% lethal concentration (LC50) was determined. The animals were then stressed for seven days before being treated with different doses of baicalein (1 and 2 mg/L) for another seven days in UCS condition. Due to acute stress and UCS, the frequency of entrances and time spent in the 1) top region and 2) light area of the novel tank reduced significantly, indicating the existence of elevated anxiety levels. The biological activity of baicalein was demonstrated by its high LC50 values (1000 μg/mL). Additionally, baicalein administration increased the frequency of entries and duration spent in the light region, indicating a significant decrease in anxiety levels. Overall, the present results showed that baicalein has a therapeutic advantage in reversing the detrimental consequences of UCS and acute stress, making it is a promising lead molecule for new drug design, development, and therapy for stress.